Impact of preoperative comorbidities on elderly patients with esophageal squamous cell carcinoma following esophagectomy: a propensity score matching analysis - Kexun Li; Simiao Lu; Changding Li; Jie Mao; Huan Zhang; Kangning Wang; Guangyuan Liu; Yongtao Han; Lin Peng; Xuefeng Leng (Discover Oncology)
Abstract Objective Elderly patients, particularly those aged 70 and above, often present with comorbidities such as coronary heart disease (CHD), chronic obstructive pulmonary disease (COPD), diabetes mellitus (DM), and high blood pressure (HBP). These comorbid diseases complicate treatment. However, the impact of these comorbidities on survival outcomes and complications in elderly patients undergoing esophagectomy for esophageal squamous cell carcinoma (ESCC) remains under-researched. Methods This cohort study examined ESCC patients aged 70 and older who underwent esophagectomy. Patients were divided into two cohorts: those without preoperative comorbid diseases (NCD group) and those with preoperative comorbid diseases (CD group). Data were obtained from the Sichuan Cancer Hospital and Institute Esophageal Cancer Case Management Database between May 2016 and August 2021, with follow-up concluding on December 20, 2023. Results A total of 469 patients met the inclusion criteria, with 206 patients in the comorbid diseases (CD group) and 263 patients without (NCD group). The median follow-up period was 47.5 months, the median overall survival (OS) was 51.6 months and median disease-free survival (DFS) was 33.0 months, with no statistically significant difference in OS and DFS in 2 groups. The incidence of grade 3 or higher complications in the NCD and CD groups was similar, with no statistically significant difference. The most common grade 3 or higher complications were pulmonary infection, hydrothorax, anastomotic stenosis, and anastomotic leakage. Conclusions Preoperative comorbidities, including CHD, COPD, DM, and HBP, did not significantly impact the long-term survival or disease-free survival of elderly ESCC patients undergoing esophagectomy.